(untitled) (International Scientific Journal Alfraganus, 2025)
The article is devoted to the substantiation of the appropriate use of systems of unified indicators for measuring and assessing the technical and eco- nomic efficiency of lighting fixtures and outdoor lighting systems in municipalities. The currently used system of traditional indicators allows for a comparative analysis and assessment of the economic attractiveness of both individual luminaires and parts of outdoor lighting systems only based on certain comparison bases that are not comparable with each other. In addition, the traditional system used is not in- formative enough for the needs of management analysis and decision-making. The paper proposes two new concepts of unified indicators - the concept of a "conven- tional luminaire" and the concept of a "reference luminaire", based on the introduction of common comparison bases for all luminaires, regardless of their type and brand. The two new systems of indicators obtained allow for full comparability of individual indicators with each other, as well as to expand the boundaries of understanding the content of the category of technical and economic efficiency of outdoor lighting sys- tems for the needs of public administration. The results of the study can also be used for the purposes of monitoring the adequacy of the technical and economic state of outdoor lighting systems to modern requirements of the time and forecasting the pro- spects for timely modernization of individual elements of such systems. Key words: outdoor lighting system, “conventional luminaire”, “standard lumi- naire”, technical and economic efficiency, indicators, municipality, city.